El constructivismo y la teoría moral kantiana. Un ensayo sobre la objetividad de las distinciones morales - Caviglia, Alessandro (2022)
The aim of this paper is to clarify the relationship between constructivism and Kantian moral philosophy. In this sense, it begins by showing what moral constructivism is and how it is a position in metaethics that seeks to clarify the question of the objectivity of moral judgments in a better way than the traditional positions in the field: moral realism and moral anti-realism. It then deals with Kantian moral constructivism as one of the most developed and studied versions. In this way, the relationship between constructivism and the critique of reason, practical reason, and the moral autonomy of the person will be clarified. Finally, the most relevant conclusions of the study are presented.